What combinations of conditions lead to high performance of governance networks? A fuzzy set qualitative comparative analysis of 12 Sardinian tourist networks. Issue 4 (1st August 2022) - Fadda, Nicoletta; Rotondo, Federico
Abstract: This study seeks to contribute to our understanding of the complex causality of determinants of governance network performance in the field of tourism. From the literature, we identify four conditions – the formalization of coordination mechanisms, network management, network complexity and stakeholder involvement - and consider three levels of performance – network, participants and community. We use a fuzzy set qualitative comparative analysis (fsQCA) to investigate the cases of 12 Sardinian tourist networks. Our analysis shows that stakeholder involvement is a necessary condition, and that there are two configurations that lead to high network performance: formalized coordination mechanisms combined with the presence of network complexity and stakeholder involvement; and network complexity combined with the presence of stakeholder involvement and network management. The unique contribution of this article lies in the fact that it presents a theoretical integration of several "niche" domains of the network research in public management and administration and, in particular, it elaborates why tourism is a niche area. In doing so we hope this article acts as an example on how to study small to medium-sized networks in a specific sector.